Looking Within: An Examination Of African American Mental Models Of Museums - Dana Dudzinska-Przesmitzki; Robin S. Grenier (Adult Education Research Conference, 2011)
Little is known about African Americans’ mental of museums. This dearth of knowledge limits adult education scholars’ understanding of the educational needs and wants of African Americans in museum contexts. To address this gap, we conducted an interpretive qualitative study examining eight African Americans’ mental models of museums. Three themes emerged from the data. Implications and recommendations for scholars and museums are discussed.